TCP-IP Menggunakan Topologi Ring - Elpi Purnamasari; Dafairro Abbil Gunawan; Sandi Rahyadi; Bryant Reza Pahlevi; Didik Aribowo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Ring topology is a type of network topology that is used to connect a computer with other computers in a circular circuit, like a ring. Usually a ring topology only uses a LAN card to connect each computer. The function of a ring topology is to connect nodes or computers in a network so that they can share information and resources with each other. Meanwhile, TCP-IP itself is communication used by the internet community to exchange data from one computer to another computer on the internet, because this protocol is a collection of protocols (protocol suite).